Effects of Ocean Acidification on physiology, behaviour and ecology of fish - Cattano, Carlo
CO2 concentration in the atmosphere is increasing at unprecedented rate since the last 800,000 years due to rising fossil fuel combustion, industrial processes and land use by humans. By absorbing part of this gas from the atmosphere, Oceans contribute to the mitigation of climatic changes, but at the cost of greater modifications of their physical and chemical characteristics. CO2 dissolved in the seawater leads to increased bicarbonate (HCO3 -) and hydrogen ions (H+) concentrations with a consequent pH drop, a phenomenon known as Ocean Acidification (OA). If global policy will not put in force mitigation measures to reduce CO2 emissions, it is projected that partial pressure of dissolved CO2 (pCO2) will increase up to 600-700 μatm by 2050 and up to ~1000 μatm by 2100. At the same time, ocean surface pH is predicted to further drop by 0.3- 0.4 units by the end of this century. OA is considered one of the most serious threat for marine organisms and ecosystems, and this topic was the most studied field of investigation between 2000 and 2013. Several quantitative reviews based on meta-analytic approaches allowed some generalizations on the sensitivity of marine species to elevated pCO2 levels and lowered pH showing that OA expected for next decades would negatively affect survival, calcification, growth and development of a wide variety of taxa. Calcifying organisms are considered the most threatened group, as increase of hydrogen ions concentration may also determine the decrease of saturation states with respect to aragonite and calcite, two forms of calcium carbonate forms commonly used for building up organisms’ shells and skeletons. However, expected CO2 levels in the ocean may also affect several biological processes of non-calcifying organisms. In the last decade, a growing number of studies focused on the impact of elevated CO2 concentration on fish. The vast majority of these studies was conducted under controlled laboratory conditions and showed highly variable sensitivities among species, making ...